Minding the Gap: Comparing Student and Instructor Experiences with Critical Reflection - Arend, Bridget; Archer-Kuhn, Beth; Hiramatsu, Kazuko; Ostrowdun, Chris; Seeley, Janel; Jones, Adrian (Teaching and Learning Inquiry, 2021)
Critical reflection (CR) is regarded as essential for learning in higher education. Many instructors want students to reflect deeply and critically, but lament perceived deficiencies in students’ value and understanding of CR. This qualitative study explored four undergraduate courses across disciplines to appraise how instructors' perceptions of CR compared to the perceptions of their students. We uncovered similarities and differences in how instructors and students define, engage, identify, and value CR. Our findings reveal tensions around how to explain CR to students, and around different methods and meanings across disciplines and contexts with implications for practice. The findings suggest that although facilitating CR remains a challenging and often-nebulous endeavor, both instructors and students value the process and the gap may not be as insurmountable as commonly perceived.